Kesaksian Non Muslim Sebagai Alat Bukti Dalam Perkara Perceraian Menurut Hukum Islam (Studi Kasus di Pengadilan Agama Curup) - Fuadi, Ahmad (Berasan: Journal of Islamic Civil Law, 2022)
In the examination of the case in the Religious Court, the persons who file the lawsuit must bring in evidence, one of which is the evidence of witnesses. So important is the role of proof with testimony, almost in every process of examining cases there is always testimony. However, there is a case filed by the plaintiff before the trial in which the witness presented by the plaintiff is a witness who is not Muslim (Non Muslim), while in Islamic law the majority of scholars absolutely do not allow non-Muslim testimony to be heard. The issue raised in this study is "Non-Muslim Testimony as Evidence of Divorce", so that researchers know whether the reasons and legal basis of the judges in accepting non-Muslim testimony as evidence in divorce cases at the Curup Religious Court and whether the acceptance of non-Muslim witnesses as evidence for divorce cases is in accordance with Islamic Law. This research uses field research methodology (field reasearch) and library research (library reasearch) which is descriptive which uses a qualitative approach. To obtain data, the author uses observation methods, interviews, and documentation and literature studies, namely by studying books on the concept of testimony and then analyzed based on facts that occur in the field. The results of the study: The reasons and legal basis of the judges in accepting non-Muslim testimony as evidence in divorce cases are witnesses not as legal requirements, witnesses as evidence related to formal requirements related to qadlaan, witnesses meet formal and material requirements as witnesses regulated by articles 171, 172, 175, 308 paragraphs (1) and Article 309 R.Bg, that in testimony the most important thing is that the witness must give testimony as seen. This is evidenced by the oath according to the religion of witnesses, both Muslims and non-Muslims, not violating the provisions of the applicable laws and regulations. The legal basis used is Article 54 of Law Number 7 of 1989, Article 49 paragraph (1) of Law Number 3 of 2006, concerning Religious Justice, and Article 19 of Law of the Republic of Indonesia Number 48 of 2009 concerning Judicial Power. Meanwhile, the acceptance of non-Muslim witnesses as evidence for divorce cases is not in accordance with the rules of Islamic law.